Rice H2A.Z negatively regulates genes responsive to nutrient starvation but promotes expression of key housekeeping genes. (28th June 2018) - Zahraeifard, Sara; Foroozani, Maryam; Sepehri, Aliasghar; Oh, Dong-Ha; Wang, Guannan; Mangu, Venkata; Chen, Bin; Baisakh, Niranjan; Dassanayake, Maheshi; Smith, Aaron P
Abstract : In rice, gene body-localized H2A.Z plays a prominent role in repressing stress-responsive genes under non-inductive conditions, whereas H2A.Z at the transcription start site functions as a positive or negative regulator of transcription. Abstract: The H2A.Z histone variant plays a role in the modulation of environmental responses, but the nature of the associated mechanisms remains enigmatic. We investigated global H2A.Z deposition and transcriptomic changes in rice ( Oryza sativa ) upon exposure to phosphate (Pi) deficiency and in response to RNAi knockdown of OsARP6, which encodes a key component of the H2A.Z exchange complex. Both Pi deficiency and OsARP6 -knockdown resulted in similar, profound effects on global H2A.Z distribution. H2A.Z in the gene body of stress-responsive genes was negatively correlated with gene expression, and this was more apparent in response to Pi deficiency. In contrast, the role of H2A.Z at the transcription start site (TSS) was more context dependent, acting as a repressor of some stress-responsive genes, but an activator of some genes with housekeeping functions. This was especially evident upon OsARP6 -knockdown, which resulted in down-regulation of a number of genes linked to chloroplast function that contained decreases in H2A.Z at the TSS. Consistently, OsARP6 -RNAi plants exhibited lower chlorophyll content relative to the wild-type. Our results demonstrate that gene body-localized H2A.Z plays a prominent role in repressing stress-responsive genes under non-inductive conditions, whereas H2A.Z at the TSS functions as a positive or negative regulator of transcription.